A simulation study to control the oil production rate of oil-rim reservoir under different injectivity scenarios - Afshin Davarpanah; Behnam Mirshekari (Energy Reports, 2018)
Drilling thin oil layers regarding the high expenditures is always considered as the debate issue in petroleum industries to invest. Oil rim reservoirs are one kind unconventional reservoirs which are occupied with a strong aquifer and a big gas cap that provided complex conditions for producing reserve oil. The purpose of this study is to simulate the six different injectivity scenarios for one of the Iranian's oilfield to select the optimum scenario which has the most oil production. In these injectivity scenarios, different gas-oil ratios, water cut, and drilling new wells were considered in the simulator to compare each of them in more detail. Consequently, scenario 6 has the optimum volume of field oil production regarding the drilling of one horizontal well and three vertical well. That is to say that, horizontal wells due to the higher contact with the thin oil layers have led to more oil production rate and it is recommended to drill the wells in this type of reservoir horizontally.
Keywords: 330; Field oil production rate; Horizontal well; Injectivity scenarios; Oil-rim reservoirs; Simulator